2020
DOI: 10.2754/avb202089020151
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated biphenyl toxicity in the thyroid gland of wild ungulates: an in vitro model

Abstract: Polychlorinated biphenyls (PCBs) are carcinogens causing endocrine disruption. While production of PCBs is now banned, wildlife exposure still occurs due to environmental contamination. We investigated thyroid toxicity in wild ungulates using three-dimensional primary thyrocyte cultures exposed to PCB 138 for 24, 48, and 72 h at concentrations ranging within 0–3000 ng/ml. Thyrocyte viability ranged within 78.71–118.34%, 98.14–104.45%, and 84.16–106.70% in fallow deer-, mouflon-, and roe deer-derived ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…To conclude, repeated and chronic exposure of wild game ungulates to toxic metals in their natural habitat can impair their reproduction, with reproductive function perturbation initiated at the cellular/molecular level. Importantly, the present study confirmed the utility of cell culture models for extrapolating data on adverse effects of toxic substances in wildlife species, in line with the 'Three Rs' concept of animal research (Flieger et al 2016;Kovacova et al 2016;Abdelsalam et al 2020).…”
Section: Discussionsupporting
confidence: 86%
“…To conclude, repeated and chronic exposure of wild game ungulates to toxic metals in their natural habitat can impair their reproduction, with reproductive function perturbation initiated at the cellular/molecular level. Importantly, the present study confirmed the utility of cell culture models for extrapolating data on adverse effects of toxic substances in wildlife species, in line with the 'Three Rs' concept of animal research (Flieger et al 2016;Kovacova et al 2016;Abdelsalam et al 2020).…”
Section: Discussionsupporting
confidence: 86%
“…In addition, as exposure to A1254 caused a significant decrease in serum fT3 levels, it can be concluded that A1254 also has an endocrine disrupting effect in the thyroid, most possible due to disruption of hormonal feedback flow and changes in enzyme levels that metabolize thyroid hormones. Moreover, thyroidal damage, oxidative stress and/or the interactions of A1254 with thyroid hormone receptors may lead to alterations in thyroid hormone levels [16,27,34,[56][57][58][59][60][61][62][63]. However, more mechanistic studies are needed to show the exact endocrine disrupting mechanisms of different PCB congeners in the thyroid.…”
Section: Thyroid Organ Weightsmentioning
confidence: 99%
“…Imidacloprid and PM are generally considered as low toxicity substances to warmblooded mammals, but very little is known about the impact of toxic substances on heterothermic bats during hibernation. The aim of the study was to assess the toxic effect of two commonly used insecticides: PM and IMI, on bat-derived cells in culture, because cell cultures represent a unique alternative tool for studying toxin (Kovacova et al 2016;Abdelsalam et al 2020;Nemcova et al 2020) and pathogen effects (He et al 2014;Flieger et al 2016) in highly protected species. As the liver represents a biotransformation organ in the metabolism of xenobiotics, liver cells are the gold standard for toxicological testing of a wide range of chemicals (Soldatow et al 2013).…”
mentioning
confidence: 99%